New records of three species of the superfamily Pygmephoroidea (Acari: Heterostigmata) from Asia - Masoumeh Filekesh; Hamidreza Hajiqanbar; Isa Jabaleh (Persian Journal of Acarology)
A survey to study of mites associated with pomegranate in Mahvelat region, Khorasan Razavi province, northeastern Iran, in 2013 led to find three species of the superfamily Pygmephoroidea (Acari: Prostigmata: Heterostigmata) new to mite fauna of Asia. The materials have been collected from soil samples. These three species belong to three families of the mentioned superfamily as follows: Premicrodispus longicaudus Khaustov, 2006 (Microdispidae), Kerdabania variabilis Khaustov, 2009 (Neopygme-phoridae), Neositeroptes opacus Livshits, Mitrovanov & Sharonov, 1986 (Pygmephor-idae). A key to Iranian Pygmephoroidea (excluding Scutacaridae) recovered from soil samples is provided.